2006
DOI: 10.1029/2006jb004591
|View full text |Cite
|
Sign up to set email alerts
|

Curie temperatures of synthetic titanomagnetites in the Fe‐Ti‐O system: Effects of composition, crystal chemistry, and thermomagnetic methods

Abstract: [1] The present study is aimed at improving the calibration of the compositional dependence of the Curie temperature (T C ) of titanomagnetite (Tmt) on the basis of temperature-dependent magnetic susceptibility (c-T) curves measured on synthetic Tmts in the Fe-Ti-O system. In order to assess the possible influence of high-temperature cation vacancies onto the T C values, we have synthesized two types of assemblages in subsolidus conditions at 1 bar, 1100°C and 1300°C, under controlled oxygen fugacity condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
153
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 151 publications
(183 citation statements)
references
References 65 publications
23
153
0
Order By: Relevance
“…It is surprising to observe such large effects in these natural samples (DT C up to B150°C) given that previous studies have found either little or no evidence of temperature-dependent cation ordering in titanomagnetites 3,8,12 or relatively small changes in T C (DT C o40°C) arising from cation reordering 15 . The small amount of Mg and Al substitution in these titanomagnetites may have a role in the effect, but we note that a study of similarly impure synthetic titanomagnetites (Fe 2.6 Ti 0.2 Mg 0.2 O 4 ) also found no evidence for temperature-dependent cation ordering 8 .…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…It is surprising to observe such large effects in these natural samples (DT C up to B150°C) given that previous studies have found either little or no evidence of temperature-dependent cation ordering in titanomagnetites 3,8,12 or relatively small changes in T C (DT C o40°C) arising from cation reordering 15 . The small amount of Mg and Al substitution in these titanomagnetites may have a role in the effect, but we note that a study of similarly impure synthetic titanomagnetites (Fe 2.6 Ti 0.2 Mg 0.2 O 4 ) also found no evidence for temperature-dependent cation ordering 8 .…”
Section: Discussionmentioning
confidence: 76%
“…This calculated range is significantly smaller than the range that we have found experimentally. Further experimental evidence from synthetic titanomagnetites 15 and from synthetic magnesioferrites 14,18 suggests that the Stephenson 33 model substantially underestimates the effects of cation ordering on T C , probably due to (a) A rapidly cooled sample will follow the grey curve, departing from equilibrium at relatively high temperature (at the rate-dependent T close ) and quenching in a low degree of order. A slowly cooled sample will follow the black curve, departing from equilibrium at a lower temperature and quenching in a higher degree of order.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations